Rising Top-Income Persistence in Australia: Evidence from Income Tax Data - Nicolas Herault; Dean Hyslop; Stephen P. Jenkins; Roger Wilkins (Institute of Labor Economics (IZA), 2021)
We use a new Australian longitudinal income tax dataset, Alife, covering 1991–2017, to examine levels and trends in the persistence in top-income group membership, focussing on the top 1%. We summarize persistence in multiple ways, documenting levels and trends in rates of remaining in top-income groups; re-entry to the top; the income changes associated with top-income transitions; and we also compare top-income persistence rates for annual and 'permanent' incomes. Regardless of the perspective taken, top-income persistence increased markedly over the period, with most of the increase occurring in the mid-2000s and early 2010s. In the mid- to late-2010s, Australian top-income persistence rates appear to have been near the top of the range of tax-data estimates for other countries. Using univariate breakdowns and multivariate regression, we show that the rise in top-income persistence in Australia was experienced by many population subgroups.
Keywords: D31; I31; C81; 330; top incomes; income mobility; top-income persistence